DNA methylation of a PLPP3 MIR transposon-based enhancer promotes an osteogenic programme in calcific aortic valve disease. Issue 11 (2nd May 2018) - Mkannez, Ghada; Gagné-Ouellet, Valérie; Jalloul Nsaibia, Mohamed; Boulanger, Marie-Chloé; Rosa, Mickael; Argaud, Deborah; Hadji, Fayez; Gaudreault, Nathalie; Rhéaume, Gabrielle; Bouchard, Luigi; Bossé, Yohan; Mathieu, Patrick
Abstract: Aims: Calcific aortic valve disease (CAVD) is characterized by the osteogenic transition of valve interstitial cells (VICs). In CAVD, lysophosphatidic acid (LysoPA), a lipid mediator with potent osteogenic activity, is produced in the aortic valve (AV) and is degraded by membrane-associated phospholipid phosphatases (PLPPs). We thus hypothesized that a dysregulation of PLPPs could participate to the osteogenic reprograming of VICs during CAVD. Methods and results: The expression of PLPPs was examined in human control and mineralized AVs and comprehensive analyses were performed to document the gene regulation and impact of PLPPs on the osteogenic transition of VICs. We found that PLPP3 gene and enzymatic activity were downregulated in mineralized AVs. Multidimensional gene profiling in 21 human AVs showed that expression of PLPP3 was inversely correlated with the level of 5-methylcytosine (5meC) located in an intronic mammalian interspersed repeat (MIR) element. Bisulphite pyrosequencing in a larger series of 67 AVs confirmed that 5meC in intron 1 was increased by 2.2-fold in CAVD compared with control AVs. In isolated cells, epigenome editing with clustered regularly interspersed short palindromic repeats-Cas9 system containing a deficient Cas9 fused with DNA methyltransferase (dCas9-DNMT) was used to increase 5meC in the intronic enhancer and showed that it reduced significantly the expression of PLPP3 . Knockdown experiments showed that lower expression of PLPP3 in VICs promotes an osteogenic programme. Conclusions: DNA methylation of a MIR-based enhancer downregulates the expression of PLPP3 and promotes the mineralization of the AV.